DAMPAK KERJASAMA TRANSFER TEKNOLOGI INDONESIA-JERMAN TERHADAP ENERGI BIOGAS DI INDONESIA - Hilda Ferira, (2023)
This research aims to analyze the impact of technology transfer cooperation between Indonesia and Germany on the development of biogas energy in Indonesia. In this research, the author uses a qualitative approach method with an exploratory case study research type where this type of research is social research that can explain a condition in depth. The data in this study were collected through in-depth interviews with related parties. This research uses the theory of bilateral cooperation and new renewable energy with the concept of technology transfer that has a relationship, relevance and potential for significant transformation. The results of this study show that technology transfer cooperation between the two countries has a positive impact on the development of biogas energy in Indonesia. Despite some obstacles in the cooperation process, the researcher managed to identify long term benefits for both countries. Germany can promote its globally competitive technology while Indonesia can develop a sustainable source of clean energy. Keywords: Bilateral Cooperation, Technology Transfer, Biogas Energy